Weight loss in post-chemoradiotherapy head and neck cancer patients - Abu Zaid, Zalina; May, Kay Neoh; Mat Daud, Zulfitri Azuan; Md Yusop, Nor Baizura; Ibrahim, Zuriati; Abdul Rahman, Zuwariah; Jamhuri, Norshariza; Abdul Azim, Aishah Zafirah (MDPI AG, 2022)
Background: Weight loss is well-known among head and neck (HNC) patients during radiotherapy and could continue after the treatment is completed. Weight monitoring is essential for treatment outcomes and cancer surveillance. The purpose of the study is to evaluate the weight loss during and post-treatment among HNC patients. Methods: A total of 45 out of 50 patients post-treatment were included in this secondary treatment. Data were collected at baseline, at the completion of radiotherapy and one month after completion of radiotherapy. Results: The mean weight loss was 4.53 ± 2.87 kg (7.4%) during treatment and 1.38 ± 2.65 kg (2.1%) post-treatment. There were significant improvements one month after completion of radiotherapy in Patient-Generated Subjective Global Assessment (PGSGA), muscle mass, nutrition impact symptoms (NIS) score, energy and protein from oral intake (p < 0.0001). Energy and protein from oral nutritional supplements (ONS) decreased significantly (p < 0.0001). Conclusions: The results of this study underline the importance of early identification and monitoring post-treatment in HNC patients. The post-treatment recovery stage is very important for HNC patients to ensure a healing process.